Effect of light intensity and iron (Fe2+) concentration on growth of microcytis aeruginosa isolated from Laguna de Bay, Philippines - Rosales, Cristina Amor Mendoza (2008)
Cynobacteria is one of the major sources of toxins in freshwater. These microorganisms are highly adaptive to changing environmental conditions. In this study, the occurrence of toxin producing cyanobacteria in Laguna de Bay and the effects of light intensity (0-1700 lux) and Iron (Fe2+) concentration in its growth were determined. Microcystis aeruginosa occurred in Laguna de Bay during the moths of January-Febrauary 2006, July 2006, May-June 2007, and August 2007-March 2008. Based on the data during these months, the M.aeruginosa cell density is positively correlated with Nitrate (NO3) and Iron (Fe2+) with correlation coefficient of +0.72972 and +0.91063, respectively. It is negatively correlated with occurrence of sunshine (in days) and turbidity with correlation -0.79055 and -0.93531, respectively. Under controlled conditions, the highest population of M. aeruginosa was attained at 0.600 ppm Iron (Fe2+) concentration with maximum light condition of 1200-1700 lux. At this condition, the maximum population density of Microcystis aeruginosa was 8,95,000 cells per ml of media, which was observed after 10 days of incubation. Thus, light as an energy source, which drives photosynthesis reaction, and Iron (Fe2+) which served as catalysts, are important factors that determine blooms M. aeruginosa.
"November 2008."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Microcystis aeruginosa -- Analysis -- Laguna de Bay (Philippines).; Cyanobacterial blooms -- Monitoring -- Laguna de Bay (Philippines).; Cyanobacteria -- Identification -- Laguna de Bay (Philippines).